UTILITARIANISM VERSUS THE PRIVILEGING OF SPEECH - Terence Rajivan Edward (IJRDO - Journal of Social Science and Humanities Research, 2022)
Apparently, the Western philosophical tradition has (wrongly) preferred speech over writing – so claims Jacques Derrida. In this paper, I consider whether utilitarianism involves such a preference. There are at least two arguments against the claim.